FAKTOR YANG BERHUBUNGAN ANTARA PERILAKU PENCARIAN PENGOBATAN GEJALA GREEN TOBACCO SICKNESS (GTS) DENGAN PETANI TEMBAKAU DI KECAMATAN BANSARI KABUPATEN TEMANGGUNG - Vita Permatasari; Syamsulhuda Budi Musthofa; Priyadi Nugraha Prabamurti (Jurnal Kesehatan Masyarakat (Undip), 2020)
A large amount of tobacco production in Temanggung Regency has made it dubbed the 'City of Tobacco'. One of the districts with the highest tobacco production and the number of farmers is Bansari District. A large number of tobacco farmers can’t be separated from the risk of disease, one of which is Green Tobacco Sickness (63.7%). But not all farmers understand what Green Tobacco Sickness is and how to treat it. This study aims to analyze the factors of health-seeking behavior of Green Tobacco Sickness symptoms in tobacco farmers in Bansari District, Temanggung Regency. The research used descriptive analytic with a cross-sectional approach. Samples were selected using by multistage random sampling technique and 100 respondents were obtained. This study uses univariate and bivariate analysis. Most respondents didn't seek treatment (43.0%) because they could heal singly (31.0%), could still work (10.0%) and didn't want to seek treatment (2.0%). Analysis results obtained knowledge (p = 0.004), perceived benefits (p = 0.000), perceived obstacles (p = 0.003), self-efficacy (p = 0.000), family and friend support (p = 0.002) were related to health-seeking behavior of Green Tobacco Sickness symptoms in tobacco farmers in Bansari District. The presence of a mobile health center can reduce barriers in maximizing to health-seeking behavior in tobacco farmers.